North Florida Gardening Calendar - Sydney Park Brown (EDIS, 2012)
Give cold-damaged palms proper care to encourage their recovery in February. In April, monitor landscape plants weekly for aphids on tender new growth. Annuals that can take full sun during hot summer months include celosia, portulaca, vinca, and some coleus. In September, plant cool-season vegetable crops, such as radish, carrot, cabbage, and lettuce. This 10-page fact sheet tells what to plant and what to do in your north Florida garden year-round. Written by Sydney Park Brown, and published by the UF Department of Environmental Horticulture, April 2012.